From Sea to Shining Sea and the Great Plains to Patagonia: A Review on Current Knowledge of Diabetes Mellitus in Hispanics/Latinos in the US and Latin America - Avilés-Santa, M. Larissa; Colón-Ramos, Uriyoán; Lindberg, Nangel M.; Mattei, Josiemer; Pasquel, Francisco J.; Pérez, Cynthia M. (Frontiers in Endocrinology, 2017)
The last two decades have witnessed many advances in the prevention, treatment, and control of diabetes mellitus and its complications. Increased screening has led to a greater recognition of Type 2 diabetes mellitus (Type 2 DM) and prediabetes; however, Hispanics/Latinos, the largest minority group in the U.S., have not fully benefited from these advances. The Hispanic/Latino population is highly diverse in ancestries, birth places, cultures, languages, and socioeconomic backgrounds, and it populates most of the Western Hemisphere. In the U.S., the prevalence of diabetes mellitus varies among Hispanic/Latino heritage groups, being higher among Mexicans, Puerto Ricans, and Dominicans, and lower among South Americans. The risk and prevalence of diabetes among Hispanics/Latinos are significantly higher than in non-Hispanic Whites, and nearly 40% of Hispanics/Latinos with diabetes have not been formally diagnosed. Despite these striking facts, the representation of Hispanics/Latinos in pharmacological and non-pharmacological clinical trials has been suboptimal, while the prevalence of diabetes in these populations continues to rise. This review will focus on the epidemiology, etiology and prevention of Type 2 DM in populations of Latin American origin. We will set the stage by defining the terms Hispanic, Latino, and Latin American, explaining the challenges identifying Hispanics/Latinos in the scientific literature and databases, describing the epidemiology of diabetes - including Type 2 DM and gestational diabetes (GDM)- and cardiovascular risk factors in Hispanics/Latinos in the U.S. and Latin America, and discussing trends, and commonalities and differences across studies and populations, including methodology to ascertain diabetes. We will discuss studies on mechanisms of disease, and research on prevention of Type 2 DM in Hispanics/Latinos, including women with GDM, youth and adults; and finalize with a discussion on lessons learned and opportunities to enhance research, and, consequently, clinical care oriented towards preventing Type 2 DM in Hispanics/Latinos in the U.S. and Latin America.